2013
DOI: 10.1038/nature12471
|View full text |Cite
|
Sign up to set email alerts
|

Wapl is an essential regulator of chromatin structure and chromosome segregation

Abstract: Mammalian genomes contain several billion base pairs of DNA that are packaged in chromatin fibres. At selected gene loci, cohesin complexes have been proposed to arrange these fibres into higher-order structures, but how important this function is for determining overall chromosome architecture and how the process is regulated are not well understood. Using conditional mutagenesis in the mouse, here we show that depletion of the cohesin-associated protein Wapl stably locks cohesin on DNA, leads to clustering o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
391
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 333 publications
(443 citation statements)
references
References 45 publications
(59 reference statements)
42
391
0
Order By: Relevance
“…In Xenopus the dosage of cohesin complexes on chromosomes influences the final shape of the condensed chromosome, probably by antagonizing the activity of the condensin II complex [79] (metazoans have multiple condensin type complexes -reviewed by Hirano [66]). It has now being shown in mammalian cells that deletion of the cohesin regulator Wapl causes premature chromosome condensation in interphase and extensive chromosome bridging in anaphase [80]. Wapl is normally required for the pre-anaphase release of DNA bound cohesin complexes so its deletion leads to the stabilization of cohesin on DNA [81,82].…”
Section: Eukaryotic Chromosome Compactionmentioning
confidence: 99%
“…In Xenopus the dosage of cohesin complexes on chromosomes influences the final shape of the condensed chromosome, probably by antagonizing the activity of the condensin II complex [79] (metazoans have multiple condensin type complexes -reviewed by Hirano [66]). It has now being shown in mammalian cells that deletion of the cohesin regulator Wapl causes premature chromosome condensation in interphase and extensive chromosome bridging in anaphase [80]. Wapl is normally required for the pre-anaphase release of DNA bound cohesin complexes so its deletion leads to the stabilization of cohesin on DNA [81,82].…”
Section: Eukaryotic Chromosome Compactionmentioning
confidence: 99%
“…Since the turnover of chromosome-bound cohesin is ~20 minutes 23,24 , constant loading is required for its presence on DNA. We achieved efficient deletion of Nipbl in non-dividing hepatocytes by using a liver-specific, tamoxifen-inducible Cre driver (Fig.…”
mentioning
confidence: 99%
“…However, for reasons that are not yet understood, ctf7 plants can be obtained at low frequencies; the plants are dwarf, exhibit severe developmental abnormalities, and are completely sterile (Bolaños-Villegas et al, 2013). Inactivation of WAPL results in lethality in Drosophila melanogaster, nematodes (Caenorhabditis elegans), and animal cells (Vernì et al, 2000;Kamath et al, 2003;Tedeschi et al, 2013); however the growth of wpl1/rad61 yeast mutants is indistinguishable from the wild type (Bennett et al, 2001). Similar to the situation in yeast, WAPL inactivation in Arabidopsis has very little effect on growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…This led to the suggestion that Pds5 and Ctf7/ Eco1 promote condensation through a common WAPL-mediated mechanism regulated by Rad51 (Tong and Skibbens, 2015). Mouse cells depleted for Wapl contain partially condensed chromosomes with regions of hypercondensed heterochromatin (Tedeschi et al, 2013). It is has been suggested that this could be due in part to a failure to remove catenates during late prophase.…”
Section: Proper Cohesin Levels Are Essential For Meiotic Chromosome Smentioning
confidence: 99%